Necessity of socialization of SME in Ukraine - Suchkov, Artem (Management and Entrepreneurship: Trends of Development, 2017)
Social responsibility is the idea that businesses should balance profit-making activities with activities that benefit society; it involves developing businesses with a positive relationship to the society in which they operate.The International Organization for Standardization (ISO) emphasizes that the relationship to the society and environment in which businesses operate is a critical factor in their ability to continue to operate effectively. It is also increasingly being used as a measure of their overall performance.Social responsibility means that individuals and companies have a duty to act in the best interests of their environments and society as a whole. Social responsibility as it applies to business is known as corporate social responsibility (CSR). Many companies, such as those with "green" policies, have made social responsibility an integral part of their business models.Additionally, some investors use a company's social responsibility, or lack thereof, as an investment criterion. As such, a dedication to social responsibility can actually turn into profits, as the idea inspires investors to invest and consumers to purchase goods and services from the company. Put simply, social responsibility helps companies develop a good reputation.Purpose of the article is to study the issue of enhancing the social function of SME in Ukraine.Approach of the research are system and comparative methods, institutional and structural-functional approaches are used.Findings of the study highlights the necessity of activation of the social function in the activities of Ukrainian SME.Research limitations/implications lies in the study of the need to improve the social responsibility activities of domestic SME.Originality/value. This will contribute to the solution of social problems in the country, improving the competitiveness of domestic SME and creating a positive image of the Ukrainian small business.